Integrated multidisciplinary analysis of mobile digital radiographic acquisitions of the mummies of the hermits from the Sanctuary of Madonna della Corona (Trentino-Alto Adige, Italy – 17th to 19th century CE) - Omar Larentis; Omar Larentis; Omar Larentis; Ilaria Gorini; Michele Campus; Marta Lorenzetti; Giancarlo Mansueto; Susanna Bortolotto; Emanuele Zappa; Andrea Gregorini; Laura Rampazzi; Stefano Vanin; et al. (Frontiers in Medicine)
Paleoradiology has become a standard diagnostic method in the study of mummified or embalmed bodies. Among the various available techniques, computed tomography valuing for its ability to provide detailed information. However, computed tomography equipment is not always accessible to research teams, cannot be easily transported to all conservation sites, and raises health concerns. Therefore, mobile digital radiographic technology is often the most suitable investigative tool in specific contexts. In this study, three mummies preserved at the Sanctuary of Madonna della Corona, perched on a cliff above the Adige River Valley on the Monte Baldo at an elevation of 775 m a.s.l., were analyzed using radiographic techniques. The impossibility of transferring the bodies due to the sanctuary’s remote location imposed the use of lightweight, portable equipment for the radiological examination. This article highlights next-generation X-ray technology utility, potential, and limitations in investigating clothing fabrics, restoration history, taphonomy, entomology, anthropology, and paleopathology. The interdisciplinary approach in this study has unveiled new historical and biological insights about these mummies, which, though revered in popular devotion, had previously been unknown to both Italian and international scientific communities.